2020
DOI: 10.26508/lsa.202000955
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of immune dysfunction in COVID-19 patients allows early prediction of disease progression

Abstract: With a rising incidence of COVID-19–associated morbidity and mortality worldwide, it is critical to elucidate the innate and adaptive immune responses that drive disease severity. We performed longitudinal immune profiling of peripheral blood mononuclear cells from 45 patients and healthy donors. We observed a dynamic immune landscape of innate and adaptive immune cells in disease progression and absolute changes of lymphocyte and myeloid cells in severe versus mild cases or healthy controls. Intubation and de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 67 publications
3
48
0
Order By: Relevance
“…Indeed, chronic stimulation with IL-15 has been shown to drive NK cell dysfunction, partly via epigenetic reprogramming [ 52 ]. Another feature of severe COVID-19, first reported by Maucourant and colleagues and later confirmed in two other independent studies, is the expansion of adaptive-like NK cells [ 13 •• , 24 , 53 ]. Adaptive-like NK cell expansions were originally described in response to cytomegalovirus (CMV) infection [ 54 ], are characterized by high expression of NKG2C, CD57, and inhibitory self-KIR receptors [ 55 ] and undergo epigenetic reprogramming during their differentiation [ 56 ].…”
Section: Covid-19 Pathogenesis Nk Cells and Unconventional T Cellsmentioning
confidence: 81%
“…Indeed, chronic stimulation with IL-15 has been shown to drive NK cell dysfunction, partly via epigenetic reprogramming [ 52 ]. Another feature of severe COVID-19, first reported by Maucourant and colleagues and later confirmed in two other independent studies, is the expansion of adaptive-like NK cells [ 13 •• , 24 , 53 ]. Adaptive-like NK cell expansions were originally described in response to cytomegalovirus (CMV) infection [ 54 ], are characterized by high expression of NKG2C, CD57, and inhibitory self-KIR receptors [ 55 ] and undergo epigenetic reprogramming during their differentiation [ 56 ].…”
Section: Covid-19 Pathogenesis Nk Cells and Unconventional T Cellsmentioning
confidence: 81%
“…Although our study confirmed earlier reported findings and added new details on the diurnal differences in urine analytes of TB patients, it has several limitations. Primarily, the study sample size is small and we and others 44 have used control subjects that are not age-matched, which could be treated as an important limitation of the study. Taking these findings to a population level needs additional studies, with case and controls from similar age groups.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of peripheral lymphocyte counts, including CD4+ and CD8 + T cells, B cells and NK cells, has been observed in COVID-19 patients [ 268–272 ]. Further, SARS-CoV-2 has been shown to induce a relative loss of lymphoid cells coupled with myeloid cell expansion in COVID-19 patients [ 273 ]. This reduction has been linked to disease severity and survival, as severe and fatal cases show a significant reduction compared to mild or recovered COVID-19 cases [ 274 , 275 ].…”
Section: Lymphocytopenia In Covid-19mentioning
confidence: 99%
“…A study by Notz et al reported a decrease in naïve Th cells in severe COVID-19 cases [ 284 ], which may indicate an impairment of T cell proliferation, maturation, and activation [ 285 ]. Another study performed by Rendeiro et al showed that in COVID-19 patients T cells display overexpression of exhaustion and dysfunction markers such as the v-domain Ig suppressor of T cell activation (VISTA), T cell immunoglobulin and mucin-domain containing-3 (TIM-3), lymphocyte activation gene 3 (LAG-3), T cell immunosuppressor with Ig and ITIM domains (TIGIT), and PD-1 [ 273 , 286 ]. In line with this finding, Chen et al and Sadeghi et al reported increased levels of the pro-inflammatory Th17 cells, a major source of IL-10 production [ 272 , 287 ].…”
Section: Lymphocytopenia In Covid-19mentioning
confidence: 99%